PEMODELAN SISTEM IDENTIFIKASI PEMBICARA DENGAN MFCC DAN SUPPORT VECTOR MACHINE - Luthfan Almanfaluthi; Agus Buono Buono; Yani Nurhadryani (Institut Bisnis Muhammadiyah Bekasi, 2022)
In this paper, we focus on speech recognition where speakers used text-dependent which means the text is agreed in advance and will be used next. This system uses MFCC as feature extraction and SVM as pattern recognition. Data were taken from 10 adult speakers with differences in gender, age, and ethnicity. Each speaker provides 50 ballots